Testing for IIA with the Hausman-McFadden test - Wim P. Vijverberg (Institute for the Study of Labor (IZA), 2011)
The Independence of Irrelevant Alternatives assumption inherent in multinomial logit models is most frequently tested with a Hausman-McFadden test. As is confirmed by many findings in the literature, this test sometimes produces negative outcomes, in contradiction of its asymptotic x2 distribution. This problem is caused by the use of an improper variance matrix and may lead to an invalid statistical inference even when the test value is positive. With a correct specification of the variance, the sampling distribution for small samples is indeed close to a x2 distribution.
urn:nbn:de:101:1-201107133399
Keywords: C12; C35; 330; multinomial logit; IIA assumption; Hausman-McFadden test